2008
DOI: 10.1021/la8021722
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Configuration Change of Pyridine on Ge(100): Dependence on Exposure Amount

Abstract: The variations of adsorption configurations of pyridine on Ge(100) as a function of exposure amount have been studied using high-resolution photoelectron spectroscopy (HRPES). At low exposure the C 1s and N 1s core levels show a single adsorption state of pyridine with N 1s binding energy at 400.85 eV and C 1s binding energies at 286.7 and 285.9 eV, respectively. Those are attributable to Ge-N dative bonding of pyridine through the lone pair electrons of its N atom, which is consistent with previous STM and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
4
15
0
1
Order By: Relevance
“…We expect these bondings to be formed from the metastable dative bonded adsorption state before the dative bonded molecules undergo N-H dissociation. This conclusion agrees well to recently published observations by Bae et al 41 who investigated pyridine molecules adsorbed on Ge(100) surfaces and found a dative N-Ge bonding which is followed by C-Ge bondings.…”
Section: A Adsorption Configuration Of Pyrrole On Ga-rich Gaas(001) supporting
confidence: 94%
See 1 more Smart Citation
“…We expect these bondings to be formed from the metastable dative bonded adsorption state before the dative bonded molecules undergo N-H dissociation. This conclusion agrees well to recently published observations by Bae et al 41 who investigated pyridine molecules adsorbed on Ge(100) surfaces and found a dative N-Ge bonding which is followed by C-Ge bondings.…”
Section: A Adsorption Configuration Of Pyrrole On Ga-rich Gaas(001) supporting
confidence: 94%
“…Those molecules that do not experience N-H dissociation can additionally form covalent bonds from the C atoms to the As and/or Ga atoms to the surface as similarly reported by Bae et al for the adsorption of pyridine on the Ge(100)-(2 × 1) surface. 41 As described above, the GaAs surface reconstructions differ in terms of the occupation of the respective dangling bonds as a consequence of their different stoichiometries. At the As-rich phase, the GaAs(001) surface provides only filled dangling bonds which are to be regarded as nucleophilic sites.…”
Section: Discussionmentioning
confidence: 97%
“…11 Dative-bonded adducts are frequently observed only at low gas exposure and at low temperatures. It is generally believed that the adsorption occurs in a first step through a dative bond followed by the apparition of other structures 8,10,12,13 leading to the vanishing of dative bonds. It is not clear if this transformation is due to a thermodynamic constraint or to a kinetic mechanism.…”
Section: A Goal Of the Present Papermentioning
confidence: 99%
“…As similar structures to a Co–N center, N1s binding energies of Ge–N coordination by pyridine and protonated pyridine were reported to be 400.85 and 401.2 eV, respectively. 37 , 40 The previous reports suggested that the coordination of other elements to pyridine resulted in the positive shift of N1s binding energy to compare with a 398.9 eV of pyridine, which suggested the assignment of the 400.3 eV peak to Co–N bonds.…”
Section: Resultsmentioning
confidence: 95%